Analisis Peran Pemerintah Desa dalam Pengelolaan Pariwisata Model Community Based Tourism (CBT) di Desa Pengudang Kecamatan Teluk Sebong Kabupaten Bintan - Usman Siam, Nurbaiti; SANOPAKA, ENDRI; ABUMANSHUR MATRIDI, RAJA; Arfa, Desmayeti; Sahona, Sahona (STISIPOL Raja Haji, 2022)
Community based tourism (CBT) is a concept of tourism management that is closely related to the active participation of communities in tourism development. targets the active roles of communities This form of CBT tourism is organized and owned by communities for the community to help tourists to increase their awareness and learn about local communities and life ordinances.The purpose of this study is basically to know how the management and the role of the village government in CBT management in the village of Telok Sebong Sub-district persecutor Bintan Regency. In this study, the informants consisted of 5 POKDARWIS managers and 2 villager representative. The data analysis technique used in this study is a qualitative descriptive method with a sampling technique. The results of the study concluded that the management of community-based tourism or CBT in Pengudang Village, Telok Sebong District, Bintan Regency has not been maximized because there are still many things that need to be improved.The suggestions given so that Community-Based Tourism in Pengudang Village runs well are increasing the function of BUMDes by paying attention to all POKDARWIS, improving facilities, conducting regular tourism management training, the need for intensive promotions and in hearings activities must include discussion of CBT tourism evaluation.